PENERAPAN STRATEGI PROMOSI MELALUI MEDIA SOSIAL TIKTOK PADA UMKM BINAAN KADIN KOTA BANDUNG - Susilawati, Erna (JURNAL PENGABDIAN KEPADA MASYARAKAT (ADI DHARMA), 2024)
The world economic began to grow after the Covid-19 Pandemic. The existence of the internet and increasingly sophisticated technological developments also have a significant impact on the development and growth of the world economy. One of them is social media which is now used not only as a communication tool but also as a promotional tool. Social media is in great demand by people of all ages, making it a very profitable platform for promoting goods/services. The number of followers or viewers on a social media application will have an impact on the number of people who will see advertisements or promotions for the goods/services being marketed. One of the social media applications that is popular at the moment is Tiktok. Initially, this application was only for entertainment, containing hit songs and people dancing. However, now it is starting to be used as a place to promote goods or services, both live and not. This is very popular with the public and people can buy the products or services offered directly while they are live. Of course, this can be very profitable if applied to MSMEs assisted by the Bandung City Chamber of Commerce and Industry, because with minimal capital you will get big profits where your products will soon be known to the general public and can increase sales.